The effect of layer number on mechanical properties and dimensional stability of Hybrid Kenaf-Glass Fiber Unsaturated Polyester Composite - Nor Azian Mohamad (School of Materials Engineering, University Malaysia Perlis, 2014)
Hybrid kenaf-glass fiber unsaturated polyester composite was prepared by hand lay-up technique. The kenaf was used in a fiber mat form.The effect of layer number of hybrid kenaf-glass fiber unsaturated polyester composite on mechanical properties and dimensional stability were studied.The effect of layer number of hybrid kenaf-glass fiber unsaturated polyester composite has shown good interfacial adhesion between matrix and fiber reinforced composite thus, increasing the tensile and flexural strength of hybrid kenaf-glass fiber unsaturated polyester composite.